Manganese supplementation increases adiponectin and lowers ICAM-1 and creatinine blood levels in Zucker type 2 diabetic rats, and downregulates ICAM-1 by upregulating adiponectin multimerization protein (DsbA-L) in endothelial cells - Burlet, Elodie; Jain, Sushil K. (Molecular and cellular biochemistry, 2017)
Blood and tissue levels of manganese (Mn) are lower in type 2 diabetic and atherosclerosis patients compared with healthy subjects. Adiponectin has anti-diabetic and anti-atherogenic properties. Impairment in Disulfide bond A-like protein (DsbA-L) is associated with low adiponectin levels and diabetes. This study investigates the hypothesis that the beneficial effects of Mn supplementation are mediated by adiponectin and DsbA-L. At 6 weeks of age, Male Zucker diabetic fatty rats (ZDF) were randomly divided into two groups: diabetic controls and Mn-supplemented diabetic rats. Each rat was supplemented with Mn (D+Mn, 16 mg/kg BW) or water (placebo, D+P) daily for 7 weeks by oral gavage. For cell culture studies, Human Umbilical Vein Endothelial Cells (HUVEC) or 3T3L1 adipocytes were pretreated with Mn (0–10 µM MnCl 2 ) for 24 h, followed by high glucose (HG, 25 mM) or normal glucose (5 mM) exposure for another 24 h. Mn supplementation resulted in higher adiponectin ( p = 0.01), and lower ICAM-1 ( p = 0.04) and lower creatinine ( p = 0.04) blood levels compared to those in control ZDF rats. Mn-supplemented rats also caused reduced oxidative stress (ROS) and NADPH oxidase, and higher DsbA-L expression in the liver ( p = 0.03) of ZDF rats compared to those in livers of control rats; however, Fe levels in liver were lower but not significant ( p = 0.08). Similarly, treatment with high glucose (25 mM) caused a decrease in DsbA-L, which was prevented by Mn supplementation in HUVEC and adipocytes. Mechanistic studies with DsbA-L siRNA showed that the beneficial effects of Mn supplementation on ROS, NOX4, and ICAM-1 expression were abolished in DsbA-L knock-down HUVEC. These studies demonstrate that DsbA-L-linked adiponectin mediates the beneficial effects observed with Mn supplementation and provides evidence for a novel mechanism by which Mn supplementation can increase adiponectin and reduce the biomarkers of endothelial dysfunction in diabetes.